Effect of solvents on photophysical properties and quenching of 2‐[3‐(1H‐benzimidazole‐2‐yl) phenyl] carbonoimidoylphenol. (29th October 2014) - Suman, G. R.; Bubbly, S. G.; Gudennavar, S. B.; Thipperudrappa, J.; Roopashree, B.; Gayathri, V.; Nanje Gowda, N. M.
Abstract: The effect of solvents of varying polarity on the absorption and fluorescence emission of the Schiff base, 2‐[3‐(1H‐benzimidazole‐2‐yl) phenyl]carbonoimidoylphenol, was studied using Lippert‐Mataga bulk polarity function, Reichardt's microscopic solvent polarity parameter and Kamlet's multiple linear regression approach. The spectral properties follow Reichardt's microscopic solvent polarity parameter better than Lippert‐Mataga bulk polarity parameter, indicating the presence of both general solute–solvent interactions and specific interactions. Catalan's multiple linear regression approach indicates the major role of solvent polarizability/dipolarity influence compared with solvent acidity or basicity. The solvatochromic effect was utilized to calculate the dipole moments of ground and excited states of the Schiff base using different methods. Bathochromic shift in the emission spectrum and the increase in dipole moment in the excited state signifies the intramolecular charge transfer character in the emitting singlet state. Fluorescence quenching by aniline was also studied in 1, 4‐dioxane and n‐butanol, and the results were analyzed using sphere of action static quenching and finite sink approximation models. Copyright © 2014 John Wiley & Sons, Ltd.